Influence of Employees Motivation on Performance of Micro Finance Institutions in Rwanda.: A case of LETSHEGO-RWANDA - Elizabeth, MUGABEKAZI (International Journal of Scientific Research and Management (IJSRM), 2022)
Currently, Human Resource Management is becoming more important because employees and their knowledge are the most important aspect affecting performance of micro financial institutions in Rwanda. Motivation is one of the most important tools of Human Resource Management. Organizations are designing motivation systems in order to encourage employees to perform as well as to attract and retain potential candidates. The main purpose of this study was to assess the impact of employee motivation on performance of micro financial institutions in Rwanda. A qualitative case study methodology was used to interview key informants as well as questionnaires were distributed to the sample of 54 respondents from LETSHEGO-RWANDA headquarter and branches in Kigali. The general objective of this study was to assess the influence of employees’ motivation on performance of micro financial institutions in Rwanda. Taking into consideration of Letshego Rwanda as the case of study. The specific objectives of this research study were to examine how salary increments influence the performance of employees in Letshego, to assess the roles of team work in enhancing performance of Letshego, to find out whether motivational packages has an impact in performance of Letshego, to assess the relationship between employee motivation strategies and micro financial institutions Performance. The study employed a descriptive cross-sectional design, and population of 54 persons was applied. Document review, questionnaire, interview, and observation methods were used to collect data, while descriptive statistics and content analysis were applied for data analysis. SPSS: Statistical Package for Social Sciences was used in this research study.